The perimeter is just p(x) = x + (3x -1) + (2x -4) = 6x +3 , for every x>0 such that x, 3x -1 and 2x + 4 satisfies the condition to be the sides of a triangle, that is, each side must be less then the sum of the other 2.
So, we must have
x < 5x + 3 => which holds for every x>0.
3x -1 < 2x + 4 => x <5
2x + 4 < 4x -1 => x > 2.5
Therefore, the perimeter is p(x) = 6x +3 for x in (2.5 , 5). For other values of x, we don't have a triangle. This is important to point out.
Since 4 is in (2.5 , 3), we do have a triagle and it's perimeter is p(4) = 6 * 4 + 3 = 27
And : -provided x, 3x -1 and
If x = 4, then the sides of the triangle are 4, 11 and 12. The important thing here is to check if this is possible. In any triangle, each side is less then the sum of the other 2. And we readily see this condtion is satisfied when x =4.
Therefore, the
2007-05-31 10:26:45
·
answer #1
·
answered by Steiner 7
·
0⤊
1⤋
sides: x, 3x-1, 2x+4
Add the 3 side lengths of a triangle to get it's perimeter.
In this case:
P(x) = x+(3x-1)+(2x+4)
simplify with like terms:
P(x) = 6x+3
When x = 4 meters...
sub 4 into your perimeter equation...
P=6(4)+3
27
When x = 4 meters, your perimeter is 27 meters
2007-05-31 10:07:10
·
answer #2
·
answered by TunaRollZ 2
·
0⤊
0⤋
just add all the sides
x + 3x - 1 + 2x + 4 = P
P = 6x + 3 or 3 ( 2x + 1)
x=4 P = 24 + 3 or 27
2007-05-31 10:06:53
·
answer #3
·
answered by golffan137 3
·
0⤊
0⤋
perimeter=x+3x-1+2x+4=6x+3
if x=4 then perimeter=6*4+3=27 meters.
2007-05-31 10:03:46
·
answer #4
·
answered by iyiogrenci 6
·
0⤊
0⤋
This really isn't as hard as it sounds.
First off, a perimiter is just the sum (addition) of all of the side lengths.
perimeter = x + (3x-1) + (2x+4)
let P(x) represent the perimeter
P(x) = 6x + 3
if x = 4
P(4) = 6*4 + 3 = 27 metres
2007-05-31 10:03:16
·
answer #5
·
answered by Joe the Engineer 3
·
0⤊
0⤋
P(x) = total length of all three sides
P(x) = x + 3x - 1 + 2x + 4
P(x) = 6x + 3
if x = 4
P(4) = 6*4 + 3
P(4) = 24 + 3 = 27 m
2007-05-31 10:03:58
·
answer #6
·
answered by mwebbshs 3
·
0⤊
0⤋
p(x)=(3x-1+2x+4+x)
or,p(x)=3(2x+1)
p(4)=3(2*4+1)=27
2007-05-31 10:03:37
·
answer #7
·
answered by Diki 1
·
0⤊
0⤋